2019
DOI: 10.3390/ijerph16193772
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Cardiorespiratory Fitness of Children and Adolescents in Urban Areas: A Panel Data Analysis of 27 Provinces in China, 1985–2014

Abstract: With rapid economic development in China, cardiorespiratory fitness (CRF) of children and adolescents is on a decline. However, this appears to have slowed down, reaching stagnation in certain areas. However, it is unclear if the change in CRF is related to economic growth and development or not. This study describes trends in CRF of Chinese children and adolescents, and empirically tests the relationships between China’s macro-economic developments and cardiorespiratory fitness of children and adolescents ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Forceful inhalation and deflation of the lungs strengthens respiratory muscles [ 36 ]. The endurance running level of Chinese urban students between 1984 and 2014 showed a U-shaped trajectory [ 20 ]. In addition, a U-shaped relationship was reported between economic growth and endurance running of children and adolescents between 1985 and 2014 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forceful inhalation and deflation of the lungs strengthens respiratory muscles [ 36 ]. The endurance running level of Chinese urban students between 1984 and 2014 showed a U-shaped trajectory [ 20 ]. In addition, a U-shaped relationship was reported between economic growth and endurance running of children and adolescents between 1985 and 2014 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the relationship between income inequality and development [ 16 ], the concept of the Kuznets curve relationship has been recently applied to explore personal health issues [ 17 ]. For instance, previous studies reported an obesity Kuznets curve [ 18 , 19 ] and a cardiorespiratory fitness Kuznets curve [ 20 ]. To predict lung function and provide empirical evidence for formulating public health policy, it is important to explore whether there is a Kuznets curve relationship between lung health and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of income level usually leads to the increase of energy consumption, and many scholars have also studied the relationship between this factor and energy intensity [44,45]. Meanwhile, income level can also affect individual health status [46,47], so this factor should be considered as one of the important factors affecting EIWB.…”
Section: Variable Selection Of Influencing Factorsmentioning
confidence: 99%
“…Panel data are a multi-dimensional type of data involving measurements over time [74]. Panel data contain observations of multiple phenomena obtained over multiple periods for the same objects [75]. Moreover, panel data are more informative than other types of data since they offer more variability and their estimates are, therefore, more efficient [8].…”
Section: Panel Datamentioning
confidence: 99%